침출수 고도처리수의 재이용을 위한 막분리 공정의 적용 - 현길수 (한국수처리학회지, 18(6), 2010)
This study was conducted to investigate the reuse of the effluent from advanced landfill leachate treatment system, which consisted of anaerobic/aerobic activated sludge process, biofilm process, and sand/GAC filtration processes. Pilot-scale plant for this experiment consists of coagulation-sedimentation process and membrane process (reverse osmosis(RO) and electrodialysis (ED) membrane). As a result, the removal efficiencies of the coagulation-sedimentation were more than 95% for Ca2+ and 75% for SiO2. This indicates the pretreatment is necessary for maximizing the efficiency of membrane process. For membrane process, the removal efficiencies of RO and ED on total dissolved solid (TDS) and ions of chlorine and calcium were more than 95%, which describes it was considerably effective in separating saline solution from the leachate contaning high salts concentration. The water quality of main stream was kept as 1st grade due to the inflow of a filtrated leachate by the membranes. This results show that a treated leachate by RO or ED process was adequate for reuse as recharge water to river. This study was conducted to investigate the reuse of the effluent from advanced landfill leachate treatment system, which consisted of anaerobic/aerobic activated sludge process, biofilm process, and sand/GAC filtration processes. Pilot-scale plant for this experiment consists of coagulation-sedimentation process and membrane process (reverse osmosis(RO) and electrodialysis (ED) membrane). As a result, the removal efficiencies of the coagulation-sedimentation were more than 95% for Ca2+ and 75% for SiO2. This indicates the pretreatment is necessary for maximizing the efficiency of membrane process. For membrane process, the removal efficiencies of RO and ED on total dissolved solid (TDS) and ions of chlorine and calcium were more than 95%, which describes it was considerably effective in separating saline solution from the leachate contaning high salts concentration. The water quality of main stream was kept as 1st grade due to the inflow of a filtrated leachate by the membranes. This results show that a treated leachate by RO or ED process was adequate for reuse as recharge water to river. KCI Citation Count: 2